Bucket list - Zadan, Craig; Reiner, Rob.; Zackham, Justin, 1970-; Nicholson, Jack.; Freeman, Morgan; Hayes, Sean, 1970-; Todd, Beverly, 1946-; Freeman, Alfonso; King, Rowena; Morrow, Rob.; Warner Bros. Pictures (1969- ); Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2008)
Corporate billionaire Edward Cole and working class mechanic Carter Chambers have nothing in common, except they both have been diagnosed with terminal illnesses. While sharing a hospital room together, they decide to make a Bucket List of all the things they have ever wanted to do before they die. In the process of completing the list, both of them heal each other, become unlikely friends, and ultimately find the joy in life.
Special features: Widescreen version presented in a "matted" vormat ; Standard version -- "Writing a Bucket List" with screenwriter Justin Zackham -- John Mayer "Say" music video -- Language: English Dolby surround 5.1 ; Frency dolby surround 5.1 ; Spanish Dolby surround 5.1 -- Subtitles: English, French, Spanish -- DVD-ROM Weblink [see system requirements below].
Originally released as a motion picture in 2007.
Special features: "Writing a Bucket list " with screenwriter Justin Zackham; music video "Say" by John Mayer.
Jack Nicholson, Morgan Freeman, Sean Hayes, Beverly Todd, Alfonso Freeman, Rowena King, Rob Morrow.
DVD, region 1, full screen (1.33:1) and widescreen (1.85:1) presentations; Dolby Digital.
Keywords: Cancer -- Patients -- United States; Cancer in men -- United States; Lists; Older men -- United States; Cancer -- Pacientes -- Estados Unidos; Aventuras -- Estados Unidos; Adventure; Cancer -- Patients -- United States; Cancer in men -- United States; Lists; Older men -- United States; Feature films; Comedy films; Action and adventure films; Video recordings for the hearing impaired; Feature films; Comedy films; Adventure films; Comedy; Adventure